Extrolites of Aspergillus fumigatus and Other Pathogenic Species in Aspergillus Section Fumigati - Frisvad, Jens C.; Larsen, Thomas O. (Frontiers in Microbiology, 2016)
Aspergillus fumigatus is an important opportunistic human pathogen known for its production of a large array of extrolites. Up to 63 species have been described in Aspergillus section Fumigati, some of which have also been reliably reported to be pathogenic, including A. felis, A. fischeri, A. fumigatiaffinis, A. fumisynnematus, A. hiratsukae, A. laciniosus, A. lentulus, A. novofumigatus, A. parafelis, A. pseudofelis, A. pseudoviridinutans, A. spinosus, A. thermomutatus, and A. udagawae. These species share the production of hydrophobins, melanins, and siderophores and ability to grow well at 37°C, but they only share some small molecule extrolites, that could be important factors in pathogenicity. According to the literature gliotoxin and other exometabolites can be contributing factors to pathogenicity, but these exometabolites are apparently not produced by all pathogenic species. It is our hypothesis that species unable to produce some of these metabolites can produce proxy-exometabolites that may serve the same function. We tabulate all exometabolites reported from species in Aspergillus section Fumigati and by comparing the profile of those extrolites, suggest that those producing many different kinds of exometabolites are potential opportunistic pathogens. The exometabolite data also suggest that the profile of exometabolites are highly specific and can be used for identification of these closely related species.